Petrified pinna in a porter: a case report - Ulaganathan, Prabhakar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
This case report examines a rare instance of acquired petrified ear, a condition characterized by calcification or ossification of the auricular cartilage, potentially attributable to chronic mechanical pressure in an occupational setting. The study details the clinical presentation and radiological findings of a 50-year-old market porter who routinely carried heavy loads on their left shoulder, resulting in persistent compression of the left ear. Physical examination revealed a rigid, thickened, and smaller left pinna compared to the right. The patient did not report any associated pain. The patient had no history of trauma or metabolic disorders. There was no hearing impairment. Imaging confirmed that the left pinna was calcified. This case suggests a strong link between chronic occupational mechanical strain and the development of petrified ear.